Transanal excision of anorectal leiomyoma, a rare location pathology: case report and review - Bustamante Silva, Ludwigvan Adriano; Velasco Cabrera, José Antonio; Aguilar Barragán, Cuauhtémoc; Ruiz Berrones, Arianna; Jaimes Durán, Edwin Michel; Gallardo Castillo, Andrés Manuel; Cazarez Huazano, Sinue (International Surgery Journal, 2022)
Gastrointestinal leiomyomas (GILM) are benign tumors truly originated in the smooth muscle of the digestive tract, therefore, they are mesenchymal tumors and can come from the muscularis propria, muscularis mucosae or from the smooth muscle of the blood vessels. These tumors occur more frequently in women and despite being the second most common mesenchymal mural tumor of the digestive tract, anorectal location is very rare, representing less than 0.1% of all anorectal neoplasms. In the present case, we reported a patient with a rectal submucosal leiomyoma that was excised using a transanal approach.